Bicycle Culture in the Bhutanese Refugee Camps - Shrestha, Tara Lal (International Research Journal of MMC, 2022)
This paper through qualitative research method documents stories of bicycle history in the Bhutanese refugee camps in eastern Nepal – the stories of the seven refugee camps – that remains in retrospections of the Bhutanese diaspora (in the countries of resettlement) more alive than in the camp. As an unofficial model of bicycle culture, the pre-third country resettlement period is examined through the aesthetics of bicycle commuting for cause in the post-third country resettlement context, when bicycling in the refugee camp is in the verge of extinction. Studying the grey literature, including the visual texts, this paper also attempts to draw the attention of the Bhutanese community, who experienced the aesthetics of bicycling then is mostly indulged in car culture in the countries they have resettled. Finally, this article presents some evidences of insights into how the Bhutanese community from the resettled countries can contribute to the bicycle culture and there are some rays of hope. The finding of this research helps to affirm bicycle activism in order to establish a sustainable bicycle culture.